Acetate transport in the S3 segment of the rabbit proximal tubule and its effect on intracellular pH (The Rockefeller University Press, 1988)
We monitored intracellular pH (pHi) in isolated perfused S3 segments of the rabbit proximal tubule, and studied the effect of acetate (Ac-) transport on pHi. pHi was calculated from the absorbance spectrum of 4',5'-dimethyl-5-(and 6) carboxyfluorescein trapped intracellularly. All solutions were nominally HCO3(-)-free. Removal of 10 mM Ac- from bath and lumen caused pHi to rapidly rise by approximately 0.2, and then to decline more slowly to a value approximately 0.35 below the initial one. Removal of only luminal Ac- caused pHi changes very similar to those resulting from bilateral removal of Ac-. When Ac- was removed from bath only, pHi rose rapidly at first, and then continued to rise more slowly. Readdition of Ac- to bath caused pHi to rapidly fall to a value slightly higher than the one prevailing before the removal of Ac- from the bath. In experiments in which Ac- was first removed from both bath and lumen, readdition of 10 mM Ac- to only lumen caused a rapid but small acidification, followed by a slower alkalinization that brought the pHi near the value that prevailed before the bilateral removal of Ac-. The alkalinizing effects caused by the readdition of 10 or 0.5 mM Ac- were indistinguishable. When Ac- was returned to only lumen in the absence of luminal Na+, there was a small and rapid pHi decrease, but no pHi recovery. Removal of Na+ from bath did not affect the pHi transients caused by the addition of Ac- to lumen. In experiments in which Ac- was first removed bilaterally, readdition of Ac- to only bath caused a large and sustained drop in pHi, whereas the subsequent removal of Ac- from the bath caused a slight alkalinization. These pHi changes caused by readdition or removal of Ac- from baths were unaffected by the absence of external Na+. We conclude that there is a Na+/Ac- cotransporter at the luminal membrane, and pathways for acetic acid transport at both luminal and basolateral membranes. The net effect of Ac- transport on pHi is to alkalinize the cell as a result of the luminal entry of Na+/Ac-, which is followed by the luminal and basolateral exit of acetic acid.